PENGARUH ONLINE CUSTEMER REVIEW DAN ONLINE CUSTOMER RATING TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA PENGGUNA APLIKASI TIKTOK SHOP DI KABUPATEN JOMBANG - Rossandy, Gesit Arga; Dwijayanti, Renny (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
This study aims to determine the effect of online customer reviews and online customer ratings on the TikTok shop application in Jombang Regency. The population used is the effect of online customer reviews and online customer ratings on purchasing decisions on the TikTok application. This study used a sample of 101 respondents. The analysis used is a research instrument test and hypothesis testing. With the results of the study that a consumer or buyer trusts the rating information in the TikTok shop more because the better the rating given, the goods received will be in accordance with the description so that they can fulfill the purchase decision at the TikTok shop and consumers trust the online customer rating given by other consumers on TikTok to determine the service provided. In addition, consumers also choose purchases based on reviews of seller services reviewed by other consumers on the TikTok shop. But consumers trust the rating information given for a product more, the higher the stars or ratings given, the more the product matches the actual situation. This can be seen from the results of the t-test that the online customer review and online customer rating variables partially influence purchasing decisions in the TikTok shop marketplace. The F test shows that the variables price, online customer review, and online customer rating simultaneously influence purchasing decisions in the Tiktok shop marketplace. The results of the coefficient of determination (R2) show that online customer review and online customer rating simultaneously influence purchasing decisions by